Synthesis and Applications of Xanthate Esters - Swaroop, Toreshettahally R; Suresh, Rajaghatta N; Umashankara, Muddegowda; Rangappa, Kanchugarakoppal S (Chemistry and Biochemistry: Research Progress Vol. 1, 2025)
We herein present a base-induced cycloaddition of active methylene isocyanides like tosyl methyl isocyanide and ethyl isocyanoacetate with xanthate esters for the synthesis of 5-(alkoxy)-4-(tosyl/ethoxycarbonyl)-1,3-thiazoles in DMF. In addition, we have explored xanthate esters as alkylating agents for amines in the presence of an acid catalyst. Finally, the reaction between xanthate esters and aryl methyl isocyanides produced carbamothioates in the presence of a base in DMF.